2004
DOI: 10.1136/jcp.2004.017566
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum insulin-like growth factor I (IGF-I) in neonatal outcome

Abstract: Aims: To determine the role of serum insulin-like growth factor I (IGF-I) in predicting the occurrence of septal hypertrophic cardiomyopathy in infants of mothers with diabetes. Methods/materials: In this prospective study, 100 pregnant women (50 with diabetes and 50 controls), matched for age and race, were studied. One intrapartum blood sample was taken at 28 weeks of gestation from both groups of mothers and another sample at delivery. All samples were analysed for maternal IGF-I by an enzyme linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
2
8
0
2
Order By: Relevance
“…IGF-I also plays an important role during gestation in placental development and function [26]. Elevated levels of IGF-I have been associated with septal hypertrophic cardiomyopathy [27]. The results from this study confirmed previous observations in Caucasian women that IGF-I levels with or without adjustment for age and BMI are higher in GDM [28].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)supporting
confidence: 82%
“…IGF-I also plays an important role during gestation in placental development and function [26]. Elevated levels of IGF-I have been associated with septal hypertrophic cardiomyopathy [27]. The results from this study confirmed previous observations in Caucasian women that IGF-I levels with or without adjustment for age and BMI are higher in GDM [28].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)supporting
confidence: 82%
“…Diabetic mothers who gave birth to infants (n ¼ 6) with neonatal septal hypertrophy had significantly (P < .01) higher IGF-1 levels than mean levels of control mothers (n ¼ 0 infants with septal hypertrophy) and also greater mean levels than that of all pooled diabetic mothers. 28 Evidence of diastolic impairment in the form of prolonged relaxation time of the myocardium prior to mitral valve opening was detected in our diabetic cohort during early to midgestation (Figure 1), which may imply increased passive stiffness of the myocardium. Passive stiffness is determined by 2 components: collagen-based stiffness of the extracellular matrix and titin-based stiffness of the microfilaments.…”
Section: Discussionmentioning
confidence: 91%
“…Em gestações complicadas pelo diabete melito são descritas alterações do sistema cardiovascular fetal em que se verifi ca aumento da espessura das paredes ventriculares e do septo interventricular [13][14][15] e também a cardiomegalia 2,16,17 . A causa da taxa de crescimento cardíaco anormal não está clara, mas pode-se relatar diferença no grau de sensibilidade do miocárdio fetal a fatores de crescimento gerados pela mãe 17 , placenta ou feto em resposta à estimulação hiperglicemiante 18 .…”
Section: Discussionunclassified
“…A causa da taxa de crescimento cardíaco anormal não está clara, mas pode-se relatar diferença no grau de sensibilidade do miocárdio fetal a fatores de crescimento gerados pela mãe 17 , placenta ou feto em resposta à estimulação hiperglicemiante 18 . Especula-se que o acelerado crescimento cardíaco e a maturação funcional do sistema nervoso autônomo parassimpático cardíaco possam estar alterados quando comparado com o desenvolvimento de fetos normais, resultando em aumento na variabilidade da FCF 16,17 . Estudos ecocardiográfi cos demonstram alterações na função cardíaca fetal a partir da 20ª semana 18,19 de gestação, estando recomendado estudo do coração fetal ao redor da 24ª semana 20 .…”
Section: Discussionunclassified